Adipose-Derived Mesenchymal Stem Cells Ameliorating Pseudomonas aeruginosa–induced Acute Lung Infection via Inhibition of NLRC4 Inflammasome - Lu-lu Li; Lu-lu Li; Ying-gang Zhu; Xin-ming Jia; Dong Liu; Dong Liu; Jie-ming Qu; Jie-ming Qu (Frontiers in Cellular and Infection Microbiology, 2021)
BackgroundPseudomonas aeruginosa (PA) is one of the most common Gram-negative bacteria causing hospital-acquired pulmonary infection, with high drug resistance and mortality. Therefore, it is urgent to introduce new non-antibiotic treatment strategies. Mesenchymal stem cells (MSCs), as important members of the stem cell family, were demonstrated to alleviate pathological damage in acute lung injury. However, the potential mechanism how MSC alleviate acute lung infection caused by PA remains unclear.ObjectiveThe purpose of this study was to investigate the effects of Adipose-derived mesenchymal stem cells (ASCs) on acute pulmonary infections and the possible mechanisms how ASCs reduce pulmonary inflammation induced by PA.MethodsThe therapeutic and mechanistic effects of ASCs on PA pulmonary infection were evaluated respectively in a murine model as well as in an in vitro model stimulated by PA and co-cultured with ASCs.Results1. ASCs treatment significantly reduced the bacterial load, inflammation of lung tissue and histopathological damage by PA. 2. PA infection mainly activated Nod-like receptor containing a caspase activating and recruitment domain 4 (NLRC4) inflammasome in the lung of mice. ASCs attenuated acute lung infection in mice by inhibiting NLRC4 inflammasome activation. 3. NLRC4−/− mice showed a significant improvement in survival rate and lung bacterial load after PA infection. 4. ASCs mainly increased expression and secretion of STC‐1 in response to PA‐stimulated NLRC4 inflammasome activation.ConclusionsPA infection attenuated macrophage phagocytosis through activation of NLRC4 inflammasome in macrophages, which eventually led to pulmonary inflammatory damage in mouse; ASCs reduced the activation of NLRC4 inflammasome in macrophages induced by PA infection, thereby increasing the phagocytic ability of macrophages, and ultimately improving lung tissue damage in mouse; ASCs may inhibit NLRC4 inflammasome through the secretion of STC-1.